2021
DOI: 10.1093/geroni/igab046.512
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 Pandemic Increased Advance Care Planning Discussions Held by Older Adults?

Abstract: In an online survey exploring older Canadians’ experiences during the COVID-19 pandemic, 3989 respondents aged 55-99 indicated whether they had discussed their future care preferences and with whom, prior to and since the outbreak. Pre-pandemic, 62% had held such discussions; since the pandemic 43% did so, 11% for the first time. Rates were significantly higher among white respondents than among persons of color, women than men, and those 65+ than younger respondents. Respondents were most likely to have talke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…At the same time, LGBT persons were slightly more likely to have received a COVID vaccine. Gutman et al [20] reported results along similar dimensions in their large study of older Canadians and their experiences during the pandemic, upon which this present study is based. That is, they found that, relative to heterosexuals in the sample, LGBT persons were more likely to report feeling anxious, depressed, and sad and more likely to report changes in access to their physical and mental healthcare.…”
Section: Lgbt Persons and Covid-19supporting
confidence: 58%
See 2 more Smart Citations
“…At the same time, LGBT persons were slightly more likely to have received a COVID vaccine. Gutman et al [20] reported results along similar dimensions in their large study of older Canadians and their experiences during the pandemic, upon which this present study is based. That is, they found that, relative to heterosexuals in the sample, LGBT persons were more likely to report feeling anxious, depressed, and sad and more likely to report changes in access to their physical and mental healthcare.…”
Section: Lgbt Persons and Covid-19supporting
confidence: 58%
“…As noted above, Gutman et al [20] extended these findings even further into the responses of LGBT persons (all over the age of 55) to the COVID-19 pandemic. They found, for example, that LGBT persons were more likely than were cisgender, heterosexual persons to wear masks, to social distance, and to follow other public health mandates proclaimed during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The COVID-19 pandemic is a historic global life event fraught with unexpected life-threatening illness and deaths, social disconnectedness, and lost livelihoods, all of which may result in mental harm [73,74]. A national online survey of Canadians 55+ years of age revealed that more in the 55 to 64 age group than those 65 and over experienced disruptions in everyday life routines ranging from work to hobbies, changes in employment, and stress and discord in the family [75]. Additionally, midlife adults were more likely than older adults to rate their overall health as worse and to experience negative emotions like sadness and a feeling of being judged.…”
Section: Discussionmentioning
confidence: 99%
“…We also wondered whether making friends might carry more weight within this context, particularly for women. Women reported experiencing greater mental harm with social distancing and lockdowns [75,97]. Perhaps then we also ought to ask: would energy and health expectations resonate more with middle-aged or older persons?…”
Section: Discussionmentioning
confidence: 99%